Growth regulation of melanoma cells by interferon and (2'-5')oligoadenylate synthetase. - Creasey, A A (1983)
We report that endogenous, as well as exogenous, interferon (IFN) regulates the growth of human melanoma cells in culture. When antibodies directed against human fibroblast IFN were incorporated into the media of high-density cells stimulated to proliferate with serum, the cells entered the cell cycle earlier than did the controls. In investigating the biochemical basis for this finding, we have found that there is an inverse relationship between the (2'-5')oligoadenylate synthetase levels and the percentage of cells in S in untreated cultures. Upon IFN treatment, the relationship is obliterated and (2'-5')oligoadenylate synthetase levels increase throughout all phases of the cell cycle. This increase in enzyme levels correlates well with the decreased probability of the IFN-treated cells to cycle. These findings suggest a biological role for IFN as a negative growth factor for cells in culture.